O entendimento de idosos hipertensos sobre a doença e as complicações advindas da não adesão ao tratamento - NASCIMENTO, Cláudia Lima do (2019)
Objective: To understand the understanding of elderly hypertensive patients about the disease and the complications of non-adherence to treatment. Methodology: This is a descriptive study of qualitative approach, conducted with 28 individuals enrolled in the Cremation Basic Health Unit in the city of Belém Data collection was conducted through semi-structured interview in the April period. to June 2016. the responses of the study subjects ace subjective questions were analyzed according to discourse analysis. He obeyed the resolution 466/2012 and was approved by the Research Ethics Committee (CEP) of the Federal University of Pará, through the opinion number 1389712. Results: Data were grouped into three study units, called "The (mis) understanding of older people on hypertension"; "The Treatment of Hypertension in the perception of the elderly" and "Complications of non-adherence to treatment of hypertension." Realized with the units that most seniors are unaware of the concepts of disease, associating it with the symptomatology of hypertensive peaks, in addition, it was found that most of the elderly understood as a treatment for hypertension medicine use, not making the combination of drugs with the lifestyle change. But there were those who reported in his speech that the treatment should be either through pharmacological measures as to healthy lifestyle habits. In contrast, most knew inform the complications that can occur due to non-adherence to treatment. Final Thoughts: We conclude that elderly hypertensive patients do not have sufficient information to be hypertension. thus realizing the importance of hypertensive elderly know this chronic disease, understanding how it happens and what can happen if there is no adherence to treatment. Therefore, it is necessary that health professionals, especially nurses, have effective communication with the patient, informing him through health education about the disease, treatment and the consequences of their non-compliance.